Onychomadesis caused by hand-foot-mouth disease. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
A 26-month-old girl was first observed for the presence of nail lesions arisen from about 1 month. The family history was negative for psoriasis and atopy. The little patient attended the kindergarten for three months. Physical examination (Fig. 1) showed alterations in the 1st, 3rd and 4th finger of the right hand. About 1.5 mm from the proximal nail border there was a fracture of the nail plate. On the thumb, distally to the fracture, the plate was partially discolored and proximally to the fracture regrowth of a normal nail could be seen, while in the 3rd and 4th finger there was transverse leuconychia distally to the fracture. A supplement of history informed us that the girl had suffered from a severe form of hand-foot-mouth disease four weeks before the onset of nail lesions. The final diagnosis was onychomadesis secondary to hand-foot-mouth disease.